Pengembangan Lms Berbasis Moodle Mengimplementasikan Pjbl Untuk Mengukur Kompetensi Administrator Database Dengan Pendekatan Joyful Learning Pada Materi Materi Basis Data (Xi Rpl Smks Semen Gresik) - Meutya Hermanadia; Bambang Sujatmiko (CV. SINAR HOWUHOWU, 2026)
Database learning for Grade XI Software Engineering (RPL) students at SMKS Semen Gresik is still predominantly conducted through conventional teaching methods, resulting in low student engagement and suboptimal achievement of Database Administrator competencies. This study aimed to develop a Moodle-based Learning Management System (LMS), namely SIJOY, by implementing the Project Based Learning (PjBL) model with a Joyful Learning approach and to examine its feasibility and effectiveness in improving students' Database Administrator competencies. This research employed the Research and Development (R&D) method using the ADDIE development model, consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The effectiveness of the developed LMS was evaluated using a Nonequivalent Control Group Design involving 60 Grade XI Software Engineering students at SMKS Semen Gresik, divided into an experimental class and a control class. The research instruments included media expert validation questionnaires, learning expert validation questionnaires, student response questionnaires, and pretest-posttest achievement tests. The data were analyzed using descriptive percentage analysis, prerequisite tests, and the Independent Samples T-Test. The results showed that the SIJOY LMS obtained feasibility scores of 95.83% from media experts and 92.85% from learning experts, both categorized as Highly Feasible. Furthermore, the Independent Samples T-Test revealed a significant difference between the experimental and control groups (t = −8.674; p < 0.001), indicating that the Moodle-based SIJOY LMS implementing Project Based Learning with a Joyful Learning approach is feasible and effective in improving students' Database Administrator competencies in Database learning.